A-scan ultrasound in ophthalmology: A simulation tool. (November 2021) - Petrella, Lorena; Perdigão, Fernando; Caixinha, Miguel; Santos, Mário; Lopes, Maria; Gomes, Marco; Santos, Jaime
Highlights: The developed tool allows simulating ophthalmological applications of A-scan ultrasounds. The tool allows evaluating diverse error sources associated to A-scan biometry. Ultrasound speed assumptions induce substantial errors in the estimate of the eye axial length. Axial resolution and low reflexion coefficient limit the identification of the retina/choroid interface. Abstract: In the present study, we developed a computational tool for simulating the ophthalmological applications of A-scan ultrasound, including cataract characterisation and biometry. A-scan biometry is used to measure the axial length (AL) of the eye before cataract surgery to calculate the refractive power of the intraocular lens to be implanted. Errors in the measurement of the AL lead to post-surgical refractive errors. The simulation tool was developed using the k-Wave Matlab toolbox, together with a user-friendly interface developed in Matlab. Diverse error sources were evaluated. Constant ultrasound speed assumptions may introduce refractive errors of up to 0.6 D; by contrast, probe positioning errors had a lower impact, of up to 0.11 D. The correct identification of the Bruch's membrane is limited not only by axial resolution constraints but also by the low reflection coefficient at the retina/choroid interface. Regarding cataract characterisation, the amplitudes of the echoes reflected at the lens interfaces are sensitive to diverse cataract types and severities, and a more realistic representation could be obtained by using a higher resolution in the eye grid; however, the required computational times would make simulations impracticable when using personal computers. The simulation tool shows good versatility for evaluating diverse aspects of A-scan biometry.